Continuation of emtricitabine/lamivudine within combination antiretroviral therapy following detection of the M184V/I HIV‐1 resistance mutation. Issue 5 (11th January 2020) - Stirrup, OT; Asboe, D; Pozniak, A; Sabin, CA; Gilson, R; Mackie, NE; Tostevin, A; Hill, T; Dunn, DT; ,
Abstract : Objectives: The aim of the study was to investigate whether lamivudine (3TC) or emtricitabine (FTC) use following detection of M184V/I is associated with better virological outcomes. Methods: We identified people with viruses harbouring the M184V/I mutation in UK multicentre data sets who had treatment change/initiation within 1 year. We analysed outcomes of viral suppression (< 200 HIV‐1 RNA copies/mL) and appearance of new major drug resistance mutations (DRMs) using Cox and Poisson models, with stratification by new drug regimen (excluding 3TC/FTC) and Bayesian implementation, and estimated the effect of 3TC/FTC adjusted for individual and viral characteristics. Results: We included 2597 people with the M184V/I resistance mutation, of whom 665 (25.6%) were on 3TC and 458 (17.6%) on FTC. We found a negative adjusted association between 3TC/FTC use and viral suppression [hazard ratio (HR) 0.84; 95% credibility interval (CrI) 0.71–0.98]. On subgroup analysis of individual drugs, there was no evidence of an association with viral suppression for 3TC ( n  = 184; HR 0.94; 95% CrI 0.73–1.15) or FTC ( n  = 454; HR 0.99; 95% CrI 0.80–1.19) amongst those on tenofovir‐containing regimens, but we estimated a reduced rate of viral suppression for people on 3TC amongst those without tenofovir use ( n  = 481; HR 0.71; 95% CrI 0.54–0.90). We found no association between 3TC/FTC and detection of any new DRM (overall HR 0.92; 95% CrI 0.64–1.18), but found inconclusive evidence of a lower incidence rate of new DRMs (overall incidence rate ratio 0.69; 95% CrI 0.34–1.11). Conclusions: We did not find evidence that 3TC or FTC use is associated with an increase in viral suppression, but it may reduce the appearance of additional DRMs in people with M184V/I. 3TC was associated with reduced viral suppression amongst people on regimens without tenofovir.